BRAC Education Program (BEP): progress report, December 2002 - May 2003 - BRAC (© BRAC, 2016)
1. BEP activities by funding sources 2. BEP organogram 3. Financial report 4. Report on unit cost of NFPE 5. EDU's achievements against work plan 6. Progress on implementation of MTR recommendations 7. LFA (Logical Framework Analysis) based progress 8. Annexure for financial report 9. Consideration of the future direction of BRAC Education Program.